The Role of Guidance and Counseling Teachers in Enhancing Students' Respect for Teachers at SMPK St. Theresia Kupang - Maria Faustina Titi; Stefanus Lio (The Future of Education Journal, 2025)
Students’ respect toward teachers is a crucial element in ensuring the success of educational processes and character formation in schools. However, contemporary social dynamics and the influence of digital media have contributed to a decline in respectful behavior among adolescents. This study aims to describe the role of Guidance and Counseling (GC) teachers in cultivating and enhancing students’ respect for teachers at SMPK St. Theresia Kupang. A qualitative descriptive method with a phenomenological approach was employed to explore students’ experiences, perceptions, and behaviors related to respectful conduct within the school environment. The findings reveal that GC teachers play a strategic role through individual counseling, group counseling, classroom guidance, and responsive services that help students regulate emotions, improve communication skills, and internalize moral values and interaction ethics. GC teachers also function as mediators in conflict situations, facilitators of character development, and role models in fostering a culture of mutual respect. The study concludes that the integration of counseling services, teacher role modeling, and school-wide habituation practices is essential in rebuilding students’ sense of respect. Therefore, GC teachers hold a significant role in creating an ethical, harmonious, and conducive school climate for effective learning.